THE RELATIONSHIP BETWEEN SELF-CONFIDENCE AND POSITIVE THINKING ON PUBLIC SPEAKING ANXIETY IN UNIVERSITY X STUDENTS IN PEKANBARU - Lailatul Izzah; Willytiyo Kurniawan; Ulya Hersa Putri; Eva Yuliza; Renny Rahmalia (Nathiqiyyah, 2024)
This research aims to examine the relationship between self-confidence and positive thinking toward public speaking anxiety. University students are required to develop public speaking skills, which help them effectively present ideas or suggestions and are valuable for their future careers. Based on literature studies, several factors influence public speaking anxiety, including self-confidence and positive thinking. This research employed a quantitative method with random sampling, involving 66 students from University X. The findings indicate a correlation coefficient (r) = 0.260, implying that both variables (X1 and X2) have an effect on Y. The most significant contributor is the self-confidence variable with a value of 0.259, followed by positive thinking with 0.008. The higher the self-confidence, the lower the anxiety in public speaking.